New insights on the natural killer cell repertoire from a thorough analysis of cord blood cells. Issue 3 (11th April 2016) - Rettman, Pauline; Willem, Catherine; David, Gaëlle; Riou, Raphaëlle; Legrand, Nolwenn; Esbelin, Julie; Cesbron, Anne; Senitzer, David; Gagne, Katia; Retière, Christelle
Abstract : Cord blood NK cell repertoire is structured early depending on KIR gene content, and contains proliferative and cytotoxic NKG2C+ NK cells skewed by HLA-E. Abstract: Although CB NK cells are characterized as immature lymphocytes, their impressive expansion and efficient graft-versus-leukemia response have been highlighted early after UCBT. To better evaluate their potential as source of effective NK cells, we revisited the study of NK cell repertoire from a large cohort of CB samples. Our study showed that the CB NK cell repertoire appears to be constructed early, depending on KIR gene content, but not on the autologous HLA environment. NKG2A was expressed on a large proportion of CB NK cells that inversely correlated with KIR + NK cell frequency. Self-HLA class I molecule–educated CB KIR + NK cells present a lower spontaneous lysis than do their adult counterparts, which is probably related to the low expression of activating NK receptors. We describe for the first time a proliferative and cytotoxic NKG2C + NK cell subset representing more than 10% of CB NK cells. NKG2A strongly inhibited CB NK cell degranulation, and its coexpression on NKG2C + NK cells may contribute to limiting their activation. Overall, the CB NK cell repertoire is constructed early and harbors numerous functional abilities shared by adult NK cells. In addition, their naïve viral status and fast expansion confer numerous advantages in immunotherapy on CB NK cells.